Outcome of preventive nursing intervention, prophylactic anticoagulation and the use of the Caprini score on venous thromboembolism after varicose vein surgery - Zheng, Ting; Zheng, Xiaofei (African health sciences, 2023)
Objective: This research was devoted to estimate the outcome of preventive nursing intervention on venous thromboembolism (VTE) after varicose vein surgery in lower extremities. Methods: A total of 516 subjects with varicose veins of lower extremities (from January 2020 to January 2022) treated in our hospital were separated into observation subgroup (n = 258) and control subgroup (n = 258) at random. The conventional nursing intervention was applied in the control subgroup, preventive nursing intervention, prophylactic anticoagulation and the use of Caprini score was applied in the observation subgroup. The levels of blood indexes [hemoglobin (Hb), platelet (PLT) and D-dimer (D-D)] were compared between the two subgroups before operation and 7 days postoperative, the occurrence of subcutaneous congestion, lower limb swelling and pain, VTE and nursing satisfaction of the subject 4 (four) weeks after discharge. Results: After intervention, the levels of PLT and D-D in the observation subgroup were notably lower than those in the control subgroup. Four weeks after discharge, the incidence of subcutaneous congestion, lower limb swelling and pain, there had no notable difference in two subgroups Versus the control subgroup, VTE in the observation subgroup was notably lower and nursing satisfaction was higher. Conclusion: Preventive nursing intervention can reduce the level of PLT and D-D, restrain in the incidence of VTE and improve the nursing satisfaction of subjects with varicose veins of lower extremities after varicose vein surgery of lower limb. Keywords: Varicose vein surgery; nursing intervention; Caprini score.